Commodifying Bali - Wohlan, Marc-Philipp (Journal of A Sustainable Global South; Vol 8 No 2 (2024): August 2024DO - 10.24843/jsgs.2024.v08.i02.p03, 2024)
Abstract Bali is not the first tropical region that has been transformed for and by a growing tourism industry. The process of commodification is speeding up exponentially, its roots arguably dating back all the way to colonial times, resulting in complications exceeding the obvious environmental issues. To grasp the situation, this article categorizes the process into three main areas. Balinese culture, including religious sites and ceremonies, art forms and symbols, as well as society and people’s psychology, Balinese natural environment, and the built environment. The realization of profit-oriented projects often disregards the immediate effects on the environment, local culture, and urban design, which is contributing to a shifting self-perception in Balinese society. Suartika and Cuthbert (2020) and Picard (1990), although thirty years apart, describe the appropriation of Balinese culture by capitalist ideas of tourism through Balinese society itself, while Suartika and Cuthbert (2018, 2020) report of a returning awareness and emerging resistance movements. Nevertheless, Balinese culture is being transformed to appeal to an international audience for economic growth. The same relates to nature along with the built environment. Conservation efforts and environmental laws are unable to decrease the environmental decay, resulting in mayor problems like pollution and water scarcity. The ongoing commodification of Bali might relate to economic growth, however, it only benefits individuals and powerful interest groups, not Balinese society. Raising awareness to the mindset that has established itself in many tourists and locals alike, through educating and speaking up, as attempted in this paper, could help change the way Bali is perceived globally. The financial means for appropriate and sustainable growth, if utilized reflectively, are given, which would ultimately help the capitalist tourism industry become the solution, rather than the problem. Excessive tourism without reflection, as observed in major touristic hotspots and in cultural heritage sites alike, is unsustainable and can ultimately lead to the collapse of the Balinese economy and environment.  Tourism, that appreciates and respects the actual culture and beauty of the island is way more beneficial to all parties involved. Index Terms — balinese society, commodification, economy, environment, perception, tourism